2020
DOI: 10.3389/fped.2020.582964
|View full text |Cite
|
Sign up to set email alerts
|

Current Approach in the Diagnosis and Management of Allergic Bronchopulmonary Aspergillosis in Children With Cystic Fibrosis

Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is a complex pulmonary disorder characterized by a hypersensitivity reaction to Aspergillus fumigatus, and almost always seen in patients with cystic fibrosis (CF) and asthma. Fungal hyphae leads to an ongoing inflammation in the airways that may result in bronchiectasis, fibrosis, and eventually loss of lung function. Despite the fact that ABPA is thought to be more prevalent in CF than in asthma, the literature on ABPA in CF is more limited. The diagnosis is cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 131 publications
(156 reference statements)
0
31
0
4
Order By: Relevance
“…Most patients with AFAD present after the fourth decade, and ABPA was regarded as rare in childhood in association with asthma, although it is well recognised in cystic fibrosis. 130 , 131 Fungal allergy is, however, a feature of severe asthma in children, and it is reasonable to assume that the sensitisation and possibly the damaging effects of AFAD start at this age. 132 Castanhinha et al found increased IL-33 expression in the airways of children with SAFS compared to non-fungal sensitised patients with therapy-resistant asthma, although they did not report how many were only sensitised to A. fumigatus rather than Alternaria and Cladosporium spp.…”
Section: Clinical Features Of Afadmentioning
confidence: 99%
“…Most patients with AFAD present after the fourth decade, and ABPA was regarded as rare in childhood in association with asthma, although it is well recognised in cystic fibrosis. 130 , 131 Fungal allergy is, however, a feature of severe asthma in children, and it is reasonable to assume that the sensitisation and possibly the damaging effects of AFAD start at this age. 132 Castanhinha et al found increased IL-33 expression in the airways of children with SAFS compared to non-fungal sensitised patients with therapy-resistant asthma, although they did not report how many were only sensitised to A. fumigatus rather than Alternaria and Cladosporium spp.…”
Section: Clinical Features Of Afadmentioning
confidence: 99%
“…Plugged and inflamed airways ultimately lead to the development of bronchiectasis [ 10 ]. The thick, golden-brown mucus expectorated, as the one seen in our case, is typical of ABPA and contains eosinophils, desquamated epithelial cells, and mucin [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remission is recognized when the patient has remained asymptomatic and with stably low IgE levels for six months after terminating corticosteroid and antifungal therapy. On the other hand, an increase in total serum IgE would represent a relapse of the disease [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations